The Role of HSP70 in the Protective Effects of NVP-AUY922 on Multiple Organ Dysfunction Syndrome in Endotoxemic Rats - Liu, Pang-Yen; Shen, Hsin-Hsueh; Kung, Ching-Wen; Chen, Shu-Ying; Lu, Chia-Hsien; Lee, Yen-Mei (Frontiers in Pharmacology, 2021)
Sepsis is defined as a life-threatening organ dysfunction syndrome with high morbidity and mortality caused by bacterial infection. The major characteristics of sepsis are systemic inflammatory responses accompanied with elevated oxidative stress, leading to multiple organ dysfunction syndrome (MODS), and disseminated intravascular coagulation (DIC). As a molecular chaperon to repair unfolded proteins, heat shock protein 70 (HSP 70) maintains cellular homeostasis and shows protective effects on inflammatory damage. HSP 90 inhibitors were reported to exert anti-inflammatory effects via activation of the heat shock factor-1 (HSF-1), leading to induction of HSP 70. We evaluated the beneficial effect of HSP 90 inhibitor NVP-AUY 922 (NVP) on multiple organ dysfunction syndrome induced by lipopolysaccharide (LPS) and further explored the underlying mechanism. NVP (5 mg/kg, i.p.) was administered 20 h prior to LPS initiation (LPS 30 mg/kg, i.v. infusion for 4h) in male Wistar rats. Results demonstrated that pretreatment with NVP significantly increased survival rate and prevented hypotension at 6 h after LPS injection. Plasma levels of ALT, CRE and LDH as well as IL-1 and TNF- were significantly reduced by NVP at 6 h after LPS challenge. The induction of inducible NO synthase in the liver, lung and heart and NF-κB p-p65 and caspase 3 protein expression in the heart were also attenuated by NVP. In addition, NVP markedly induced HSP 70 and HO-1 proteins in the liver, lung and heart after LPS injection. These results indicated that NVP possessed the anti-inflammatory and antioxidant effects on LPS-induced acute inflammation, which might be associated with induction HSP70 and HO-1, leading to prevent MODS in sepsis. NVP might be considered as a novel therapeutic strategy in the prevention of sepsis-induced MODS.